Development of Integrated Biology Teaching Materials with Al-Qur'an and As-Sunnah Values in Reproductive Materials for Class XI SMA/MA Students - Siti Robiah (Universitas Ahmad Dahlan, 2022)
This study aims to produce a product in the form of biological teaching materials integrated with the values of the Qur'an and As-Sunnah that are valid and effective in improving cognitive, psychomotor learning outcomes as well as in developing the values of faith and piety in students. This research is a Research and Development (R&D) using the ADDIE development model which consists of 5 stages, namely the analysis, design, development, implementation, and evaluation stages. Data collection techniques by observation, interviews, learning outcomes tests, and questionnaire techniques. The data analysis technique used descriptive and inferential analysis. The study results showed the developed teaching materials met the statistically valid category based on the assessment of the expert in teaching-learning, material, Islamic religious education and teachers as validators, as well as it received an extremely satisfactory response from students. Teaching materials are very effective in improving learning outcomes in term of cognitive and psychomotor, and developing the values of students' faith and piety